The effect of a succession of matches on the physical performance of elite football players during the World Cup Brazil 2014 - Soroka, A.; Lago-Penas, C. (International Journal of Performance Analysis in Sport, 2016)
The aim of the current study was to examine the influence of playing multiple games with a short recovery time between matches on physical activity in elite football. The variation of physical performance (overall distance, walking and light-intensity running, moderate-intensity running, high-intensity running and Sprint) of players during the group stage in the World Cup Brazil 2014 was examined. Footballers played three consecutive matches separated by 4 days. Altogether, 301 physical performance profiles were examined (Central Defenders (CD) = 57, External Defenders (ED) = 59, Central Midfielders (CM) = 61, External Midfielders (EM) = 56, and Forwards (F) = 68). Data were collected using a computerized multiple-camera tracking system (Prozone). No differences were found across the three matches in the distance covered in Sprint, HIR, MIR and Light-IR. External and Central Midfielders reported significant differences in the overall distance covered or that covered in MIR and HIR